Understanding next generation sequencing in oncology: A guide for oncologists. Issue 3 (December 2015) - Moorcraft, Sing Yu; Gonzalez, David; Walker, Brian A.
Highlights: We explain common concepts and terminology used in next generation sequencing. The process of DNA sequencing is summarised and different platforms compared. The steps involved in analysing sequencing data are explained. Potential applications and challenges of genetic sequencing are discussed. Abstract: DNA sequencing is now faster and cheaper than ever before, due to the development of next generation sequencing (NGS) technologies. NGS is now widely used in the research setting and is becoming increasingly utilised in clinical practice. However, due to evolving clinical commitments, increased workload and lack of training opportunities, many oncologists may be unfamiliar with the terminology and technology involved. This can lead to oncologists feeling daunted by issues such as how to interpret the vast amounts of data generated by NGS and the differences between sequencing platforms. This review article explains common concepts and terminology, summarises the process of DNA sequencing (including data analysis) and discusses the main factors to consider when deciding on a sequencing method. This article aims to improve oncologists' understanding of the most commonly used sequencing platforms and the ongoing challenges faced in expanding the use of NGS into routine clinical practice.